Risk of malignancy and the use of disease-modifying therapy in multiple sclerosis: exploring the role of DMT in a multi-center study - Bayounis, Mohammed; Bin Mahfooz, Mohammed; Assiri, Mohammed; Alghamdi, Yousef; Alturki, Fahad; Almutairi, Mahdi; Alshelawy, Abdullah; Alosaimi, Mohammed; Almutawa, Faisal; Alammar, Abdulrahman; Alyahya, Yahya; Khojah, Osama; et al. (Frontiers in Neurology, 2024)
BackgroundThe potential link between disease-modifying therapies (DMTs) and malignancy in multiple sclerosis (MS) patients has generated significant concern, particularly given the immunosuppressive nature of these treatments. Conflicting evidence in the literature has left this issue unresolved, underscoring the need for definitive research to inform clinical practice. This study addresses this gap by examining cancer occurrence among MS patients on DMTs treated at two tertiary-care centers in Saudi Arabia.ObjectivesTo report and analyze cases of malignancy in MS patients treated with DMTs and identify associated risk factors, including demographic characteristics, Expanded Disability Status Scale (EDSS) scores, treatment duration, and cumulative DMT exposure. The study also seeks to contribute to the development of evidence-based cancer screening protocols for MS patients at elevated risk.MethodsA retrospective review was performed on medical records of MS patients treated with DMTs at two tertiary-care centers in Saudi Arabia from June 2015 to December 2023. The study included 860 patients, with data collected on demographics, MS subtype, DMT usage, and subsequent cancer diagnoses. A comprehensive literature review, covering publications from February 1976 to May 2024, supplemented the review to contextualize findings within the broader research landscape.ResultsAmong the 860 MS patients on DMTs, 10 (1.16%) developed malignancies, predominantly female (80%), with an average age of 50.9 years. The majority had relapsing–remitting MS (RRMS) (90%), with interferon beta (70%) and ocrelizumab (60%) being the most frequently used DMTs. The median duration of DMT exposure prior to cancer diagnosis was 52 months. The observed malignancies included gynecological cancers, breast cancer, thyroid cancer, and nasopharyngeal carcinoma, with 60% diagnosed at advanced stages (III-IV).ConclusionThis case series highlights instances of malignancy among MS patients undergoing DMTs, suggesting a potential link that warrants further investigation. The findings underscore the need for vigilant cancer screening and patient education as integral components of MS management. The literature review reinforces the necessity for ongoing research to better understand the risks associated with DMTs, aiding in the development of more informed clinical guidelines. Further large-scale, longitudinal studies are crucial to elucidate the causality and guide safer treatment strategies.